2001
DOI: 10.1111/j.1348-0421.2001.tb02620.x
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Cleavage of Staphylococcal Exoproteins Analyzed by Two‐Dimensional Gel Electrophoresis

Abstract: Extracellular proteases of Staphylococcus aureus are emerging as potential virulence factors that are relevant to the pathogenicity of staphylococcal infections. These proteases may also be involved in the proteolytic cleavage of other exoproteins released from this organism. To define the target exoproteins and their sites of cleavage by proteases, high-resolution two-dimensional polyacrylamide gel electrophoresis followed by N-terminal amino acid sequencing of exoprotein spots was performed. Two to three hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The superantigenic exotoxins were likely rather refractory to the action of these proteases and were isolated as clear spots on a 2-DE gel after the culture. However, a few exoenzymes such as lipase and triacylglycerol lipase were detected as multiple spots, indicating probable proteolysis to generate active forms as described in the previous paper (26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The superantigenic exotoxins were likely rather refractory to the action of these proteases and were isolated as clear spots on a 2-DE gel after the culture. However, a few exoenzymes such as lipase and triacylglycerol lipase were detected as multiple spots, indicating probable proteolysis to generate active forms as described in the previous paper (26).…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal sequence of glutamic acid-specific endopeptidase (spot 4) found in strain MF330 was different from those of spots G and H of strain 2932. As our previous study showed, the multiple spots of these enzymes were generated from the proteolytic cleavage by various proteases after the protein synthesis (26). The multiple spots of toxins may be generated in a similar way by the action of own proteases, although we have had no evidence yet.…”
Section: Identification Of Exoprotein Spotsmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been considerable effort directed toward defining the S. aureus secretome (9,14,17,36,37,54,55,71,79,99,(117)(118)(119). Some of the earliest efforts were computational approaches that relied on identifying conserved features of Sec-type N-terminal signal sequences.…”
mentioning
confidence: 99%
“…Bacteria were incubated in 20 ml of LuriaBertani (LB) broth for 15 16 hr at 37 C with rotary shaking at 150 rpm, and the culture supernatant was obtained by centrifugation at 8,000 g for 15 min to precipitate bacterial cells. Total exoproteins were precipitated from the culture supernatant with 10% trichloroacetic acid (TCA) as previously described (8,18). Precipitated exoproteins were dissolved in 500 µl of immobilized pH gradient (IPG) rehydration solution (7 M urea, 2 M thiourea, 2% w/v 3-[(3-cholamidopropyl) dimethylammonio]-1-propanesulfonate (CHAPS), 0.6% w/v dithiothreitol (DTT), 0.5% v/v IPG buffer, and orange G as a tracer, and the sample solution was then adjusted to a volume of 1 ml with double distilled water.…”
Section: Methodsmentioning
confidence: 99%